(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied mutual capacitive coupling and tunneling in the silicon single electron transistor coupled to a dopant atom. We observed a spectacular enhancement of the conductance through the single electron transistor when transport occurs by resonant tunneling via the dopanant atom. We found that in certain range of temperature the mesocopic fluctuations of coulomb blockade peaks are suppressed. The coulomb blockade have equal height which is determined by the transparencies of the single electron transistor tuned barriers and it is independent of the electron motion inside the single electron transistor island. The peak height remains constant over a large number of coulomb blockade oscillations and varies weakly with the gate voltage due to the way the gate couples to the single electron transistor tunnel barriers. A strong modulation of the peak height on a scale of several coulomb balckade osciallations was considered. In silicon nanostructures based on doping modulation charge traps occur naturally at the borders of the doped regions, where the dopants are likely to diffuse away from their majority distribution and from nearly isolated charge traps. We have studied the effects associated with a single charge trap in the coulomb blocade oscillations of single electron trap. Our results are used to assess the feasibility of using single electron transistor as a means to manipulate and readout single dopant atoms in silicon. We found that at low temperatures the linear conductance can be derived from a circuit approach in which the donar single electron transistor system is replaced by a circuit of resistors. Capative and tunneling coupling were found resulting an increase of the conductance through the single electron transistor by up to one order of magnitude. The obtained results were compared with previous obtained results and were found in good agreement.